Cost-minimization analysis of individually tailored or fixed-scheduled rituximab maintenance therapy for antineutrophil-cytoplasm antibody associated vasculitides - Ana Belén Guisado-Gil; Marina Muñoz-Burgos; Ana Ortega-Eslava; Francisco Javier García-Hernández; Bernardo Santos-Ramos (Farmacia Hospitalaria)
Objective: Patients included in MAINRITSAN2 trial received either an individually tailored or a fixed-schedule therapy with rituximab as maintenance treatment of antineutrophil cytoplasm antibody associated vasculitides. The aim of this study was to compare the real-world costs of both arms. Method: We performed a cost-minimization analysis over an 18-month time period, estimating direct costs –drug acquisition, preparation, administration and monitoring costs– from the health system perspective. We conducted a number of additional sensitivity analyses with different assumptions for unit costs, with further scenarios including the interquartile range of the tailored-infusion group results, different number of monitoring visits for fixed-schedule regimen and different number of reported severe adverse events. A cost- effectiveness analysis was conducted as a sensitivity analysis using the absolute difference in the relapse rate and its confidence interval. Results: The individually tailored maintenance therapy with rituximab was shown to be a cost-saving treatment compared to the fixed-schedule therapy (6,049 euros vs. 7,850 euros). Savings resulted primarily from lower drug acquisition costs (2,861 vs. 4,768 euros) and lower preparation and administration costs (892 vs. 1,486 euros), due to the lower number of infusions per patient in the tailored-infusion regimen. The tailoredinfusion regimen presented higher monitoring costs (2,296 vs. 1,596 euros). This result was replicated in all assumptions considered in the sensitivity analysis of cost-minimization approach. Conclusions: From the perspective of the health system, the tailoredtherapy regimen seems to be the preferable option in terms of direct costs. Further studies assessing all the effects and costs associated to vasculitides maintenance treatment with rituximab are needed to support clinical management and healthcare planning.